Disentangling Differences in Homicide Incarceration Rates by Immigration Status: A Comparison in Texas - Orrick, Erin Anderson (Crime & delinquency, 2021)
Research addressing the purported relationship between immigration and crime remains popular, but some gaps remain under-explored. One important gap involves disentangling differences in crime and punishment by immigrant status, as measured across different definitions of immigration status and in relation to U.S. natives, at the individual level. Using data from Texas, results show that native-born U.S. citizens are incarcerated for homicide at higher rates than almost all immigrant groups. While the incarceration rate for undocumented immigrants was 24% greater than the rate for all foreign-citizens, this rate was significantly less than that for U.S. citizens. Among the immigrant status classifications available in this study, all were associated with lower incarceration rates for homicide than that of U.S. citizens.